Lietuvių kalbos daiktavardžių ir įvardžių dviskaitos raida - Rosinas, Albertas (Baltistica, 1994)
DEVELOPMENT OF THE CATEGORY OF DUAL NUMBER IN LITHUANIAN NOUNS AND PRONOUNS This paper attempts to prove the existence of a single-word dual number in Proto-Lithuanian (as well as in Proto-Baltic). The change of the single-word dual into a two-word dual was determined by the causes of the internal development: several forms of the single-word dual coincided with the singular forms. This process became more prominent, especially after Leskien’s law. With the emergence of a two-word dual, the single-word dual of nouns denoting „a pair of something” was the first to disappear: it was replaced by the plural form, because, due to the rules of selective restriction, the singular dual of nouns denoting „a pair of something“ could not build word groups with the numerical forms du, dvi ‘two’. The dual of nouns denothing „not a pair of something“ started to be replaced by the plural (i.e. the unmarked member) in those cases when it was no longer in the focus, i.e. when it had the feature -Fm (not first mention). However, the disappearance of the dual in Lithuanian had begun long before the introduction of the written language, and in the dialects this process is not yet over.